2006
DOI: 10.1001/archneur.63.12.1771
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic and Nicotinic Receptor Binding Differences Between Mild Cognitive Impairment, Alzheimer Disease, and Normal Aging

Abstract: Background: Neurochemical and pathologic studies show that mild cognitive impairment (MCI) is frequently a transitional state between normal aging and Alzheimer disease (AD). Neuropathologic sample sizes have been limited because relatively few individuals with MCI die before dementia develops. Decreased neocortical nicotinic receptor binding is characteristic of AD but has not been investigated in subjects with MCI.Objective: To assess nicotinic receptor binding and pathologic differences in control subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 32 publications
(19 reference statements)
1
35
0
Order By: Relevance
“…Genetic association studies investigating single nucleotide polymorphisms point to roles for cholinergic signaling components such as the synthetic enzyme ChAT, the inactivating enzyme AChE, and ␣4␤2 nAChRs in AD (Cook et al, 2004(Cook et al, , 2005Vasto et al, 2006). The most vulnerable neurons in AD seem to be those expressing high levels of nAChRs, particularly those containing the ␣7 subunit (D'Andrea and Nagele, 2006), and the numbers of nAChRs as well as some of their associated proteins change in AD (Martin-Ruiz et al, 1999;Gotti et al, 2006;Sabbagh et al, 2006). In addition, not only have ␣7 nAChRs been found colocalized with plaques (Wang et al, 2000b) but ␣7 and ␣4 subunits are also positively correlated with neurons that accumulate A␤ (Wevers et al, 1999).…”
Section: Nicotinic Acetylcholine Receptors: Structure Function mentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic association studies investigating single nucleotide polymorphisms point to roles for cholinergic signaling components such as the synthetic enzyme ChAT, the inactivating enzyme AChE, and ␣4␤2 nAChRs in AD (Cook et al, 2004(Cook et al, , 2005Vasto et al, 2006). The most vulnerable neurons in AD seem to be those expressing high levels of nAChRs, particularly those containing the ␣7 subunit (D'Andrea and Nagele, 2006), and the numbers of nAChRs as well as some of their associated proteins change in AD (Martin-Ruiz et al, 1999;Gotti et al, 2006;Sabbagh et al, 2006). In addition, not only have ␣7 nAChRs been found colocalized with plaques (Wang et al, 2000b) but ␣7 and ␣4 subunits are also positively correlated with neurons that accumulate A␤ (Wevers et al, 1999).…”
Section: Nicotinic Acetylcholine Receptors: Structure Function mentioning
confidence: 99%
“…The loss of nAChR subunits, as determined by [ 3 H]-epibatidine binding, seems to take place after the transition from mild cognitive impairment (MCI) to AD (Sabbagh et al, 2006), although the loss of epibatidine binding did not correlate with decline in memory, cognitive performance, or with the development of neurofibrillary tangles or plaques (Sabbagh et al, 2001).…”
Section: A Expression Of ␣4␤2 and ␣7 Nicotinic Acetylcholine Receptomentioning
confidence: 99%
“…Postmortem binding studies have indicated that a 4 b 2 -nAChR is the nicotinic receptor subtype that is most profoundly affected by AD (reviewed in (9)), with reductions of up to 50% in the neocortex, entorhinal cortex, and hippocampus (2,(6)(7)(8)(9)(10)(11). Decreases in regional nAChR expression have been shown to correlate with declines in cognitive function (7).…”
mentioning
confidence: 99%
“…Decreases in regional nAChR expression have been shown to correlate with declines in cognitive function (7). Evidence has accumulated that cholinergic changes, including reductions in nAChR (7,11), may be a late-stage phenomenon in AD (3,4,12). However, it remains uncertain whether the nAChR deficits occur at an early or a preclinical stage of the disease.…”
mentioning
confidence: 99%
“…These changes include reduction of nicotine and nicotinic agonist binding sites and changes in brain expression of nicotinic acetylcholine receptor (nAChR) subunits (Picciotto and Zoli 2002;Rogers et al 1998;Sabbagh et al 2006). The involvement of nAChRs in aging is also supported by multiple epidemiological studies showing the protective effect of smoking against the development of aging-associated diseases such as Alzheimer's and Parkinson's diseases (AD and PD, respectively;Elbaz and Moisan 2008;Fratiglioni and Wang 2000).…”
Section: Introductionmentioning
confidence: 99%